Changes in gait performances during walking with head movements in older adults with chronic neck pain - Madsalae, Thanya; Thongprong, Tanapat; Chaikeeree, Nithinun; Boonsinsukh, Rumpa (Frontiers in Medicine, 2024)
Background Chronic neck pain (CNP) can lead to altered gait which is worse when combined with head movement. Gait parameters for indicating speed and symmetry have not been thoroughly investigated in older adults with CNP. This study aimed to compare gait performance in term of speed and symmetry in older adults with and without CNP during walking with head movement. Methods Fifty young older adults, consisting of 36 healthy controls without neck pain (OLDs) and 14 older adults with CNP, participated in the study. Participants completed the Neck Disability Index and Activities-specific Balance Confidence Scale. The 10-Meter Walk Test (10MWT) was used to assess gait performance. Participants were instructed to walk at preferred speed under three different head movement patterns: no head movement (NM), horizontal head movement (HM), and vertical head movement (VM). The Inertial Measurement Unit was used to capture gait performance, and its software was used to analyze gait variables; gait speed, Locomotor Rehabilitation Index (LRI), gait asymmetry index, Phase Coordination Index (PCI). Results The CNP group reported moderate neck pain with mild disability in activities of daily living, and less balance confidence than the OLD group (p < 0.05). The CNP group showed significantly slower gait speed and lower LRI during walking with both the HM and VM (p < 0.05), which corresponded to lower stride length and cadence. The gait asymmetry index in the CNP group was significantly higher than the OLD group during walking with VM (p < 0.05), whereas the PCI was significantly higher than the OLD group during walking with both HM and VM (p < 0.05). Conclusion Chronic neck pain affects both speed and symmetry when walking with head movement. Gait parameters in this study could be implemented to identify changes in speed and symmetry of gait in older adults with CNP who have mild disability and high physical functioning.